1995
DOI: 10.1159/000244260
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Body Composition of the Neonate

Abstract: Obese women generally deliver heavier infants, but the body composition of these infants is unknown. The principal objective of this study was to determine if neonates of obese women have more adipose tissue. At 35–36 weeks of gestation, a fasting blood sample was collected from 37 pregnant women. Shortly after birth, the body fat of the neonates was measured with an infant total-body electrical conductivity (TOBEC) instrument using a prediction equation derived from 10 miniature pigs. At 6 weeks post partum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Maternal fat mass has been associated with maternal basal insulin concentrations in a study of 56 Swedish women by Langhoff-Roos et al 5. In a recent study by Silliman and Kretchmer18 on the relation between maternal obesity and infant adiposity in 37 subjects, a higher insulin concentration in the obese than the lean mothers was reported at 35–36 weeks of gestation.…”
Section: Discussionmentioning
confidence: 94%
“…Maternal fat mass has been associated with maternal basal insulin concentrations in a study of 56 Swedish women by Langhoff-Roos et al 5. In a recent study by Silliman and Kretchmer18 on the relation between maternal obesity and infant adiposity in 37 subjects, a higher insulin concentration in the obese than the lean mothers was reported at 35–36 weeks of gestation.…”
Section: Discussionmentioning
confidence: 94%
“…Although intrauterine environmental influences on susceptibility to obesity were first described in humans (Charney et al 1976;Chen et al 2005;Ekelund et al 2005;Laitinen et al 2001;Levin 2000;Maffeis et al 1994;Parsons et al 2001;Ravelli et al 1999;Ravelli et al 1976;Roseboom et al 2001;Silliman and Kretchmer 1995;Simmons and Breier 2002;Whitaker 2004;Whitelaw 1976), animal models hold promise for providing important insights into the underlying mechanisms. High-fat diet consumption by mothers during pregnancy and lactation has long-term consequences on offspring weight, body fat content, and orexigenic and anorexigenic neuropeptide systems (Guo and Jen 1995;Levin and Govek 1998).…”
Section: Animal Models Of Obesitymentioning
confidence: 99%
“…Infants of obese mothers have been found to have an increased degree of adiposity at birth. [92][93][94] Edwards et al 36 found that infants of obese mothers, despite higher birth weights, were not significantly more obese (length correlated with weight at or above the 75th percentile) than controls at 6 months, but were at 12 months of age. Despite this evidence of greater infantile adiposity, there is a lack of evidence to support a relationship between birth weight and adolescent obesity.…”
Section: Impact Of Obesity On Obstetrical Practicementioning
confidence: 99%